Pengaruh Model Pembelajaran Contextual Teaching And Learning (CTL) Berbasis SETS Terhadap Pemahaman Konsep Siswa Kelas IV SD Hj. Isriati Moenadi Ungaran - Sonia Lestari; Ela Suryani (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Muhammadiyah Sukabumi, 2021)
This study aims to determine the effect of the SETS-based CTL learning model on students' conceptual understanding. This type of research is using quantitative research.The research design was a quasi experiment, non equivalent control group design. The sample was taken by purposive sampling and obtained IVC class as the experimental class and IVB as the control class at SD Hj. Isriati Moenadi Ungaran. Data collection techniques using observation, questionnaires and tests. The data analysis techniques in this study were normality test, homogeneity test, simple linear regression test, t-test. The results showed: 1) There is an effect of using the SETS-based Contextual Teaching and Learning (CTL) learning model on students' conceptual understanding, this is evidenced by the significance level <0.05, namely 0.032 <0.05 and 2) There are differences in the CTL-based learning model. SETS on students' understanding of concepts using t-test with a significance value of 0.00 <0.05.